Allogeneic hematopoietic stem cell transplantation for adult patients with mixed phenotype acute leukemia: results of a matched‐pair analysis. (13th March 2015) - Shimizu, Hiroaki; Saitoh, Takayuki; Machida, Shinichiro; Kako, Shinichi; Doki, Noriko; Mori, Takehiko; Sakura, Toru; Kanda, Yoshinobu; Kanamori, Heiwa; Miyawaki, Shuichi; Okamoto, Shinichiro; Kanto Study Group for Cell Therapy (KSGCT)
Abstract Adult patients with mixed phenotype acute leukemia (MPAL) have a poor prognosis, and the therapeutic role of allogeneic stem cell transplantation (allo‐SCT) for MPAL remains to be elucidated. Thus, we retrospectively assessed the efficacy of allo‐SCT for MPAL. Eighteen patients with MPAL were identified from the transplant outcome database of Kanto Study Group for Cell Therapy (KSGCT). We also selected 215 patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) as control cohorts using an optimal matching method. The 5‐yr overall survival (OS) rate of patients with MPAL was 48.1%, and patients in remission at the time of transplant showed significantly better survival than those not in remission (5‐yr OS: 71.8% vs. 0%, P = 0.001). No significant differences were seen in OS when stratifying patients according to immunophenotype, cytogenetic abnormalities, or the type of induction therapy. The 5‐yr OS rate of patients with MPAL was not significantly different compared with AML control patients (48.1% vs. 48.1%; P = 0.855) or ALL control patients (48.1% vs. 37.8%; P = 0.426). These results suggested that allo‐SCT is an effective treatment for MPAL, especially early in the disease course, and innovative transplant approaches are warranted to improve the transplant outcome of patients with MPAL who are not in remission.